(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To establish the infraorbital nerve neurosensory disturbance (NSD) recovery trajectory using the Zuniga classification (Levels A, B, C) over 24 months following Le Fort I osteotomy (LF1O), evaluate subjective-objective correlations, and identify clinical risk factors. Methods: A prospective longitudinal cohort study enrolled 60 patients undergoing LF1O, followed at seven standardized timepoints over 24 months. Sensory function was assessed using the Visual Analog Scale (VAS) for subjective evaluation and the Zuniga classification for objective evaluation: Level A (two-point discrimination, TPD), Level B (static light touch, SLT), and Level C (pain threshold, PT). Statistical analyses included RM-ANOVA, Friedman test, Cochran’s Q, and Chi-square tests. Results: Subjective NSD peaked at 2 weeks (83.5%) and declined linearly to 2.8% at 24 months. Level C fibers fully recovered by 3 months; Level A deficits persisted in 3.33% of patients at 24 months. Age ≥25 years was the only significant risk factor delaying recovery during the acute phase (2 weeks: p = 0.035; 6 weeks: p = 0.049). Sex and surgical technique had no significant impact. VAS scores correlated strongly with Level A deficits (ρ = 0.76–0.91). Conclusion: Post-LF1O NSD predominantly follows a neuropraxic pattern with 97.2% spontaneous recovery at 24 months. Age delays early recovery but does not affect long-term outcomes. Level A assessment most accurately reflects patient-reported paresthesia and should be prioritized in long-term sensory follow-up after LF1O.